For Recipients’ Sake: Denmark-Africa Cooperation for Development - Steven Theonald P. Siahaan; Pankaj Choudhury (Fakultas Hukum, Universitas Internasional Batam, 2022)
With the rapid changes happening in the world, countries need to strengthen their cooperation to improve developments - Denmark is no exception. Denmark's development cooperation activities lie within the plan for the development of policy and humanitarian. With that in mind, African countries became Denmark's top priority in embracing shared responsibilities. In executing the work, Denmark established development cooperation with many stakeholders and local & international partners. Denmark has intensified its efforts in helping countries dealing with crises and conflicts, as these efforts are the way to achieve the Sustainable Development Goals (SDGs), mainly Goal 1 (No Poverty), 8 (Decent Work and Economic Growth), and 16 (Peace, Justice, and Strong Institutions). In achieving the goals, the Danish Government reinforces its efforts in specifically fragile countries; Ethiopia, Mali, and Somalia. Each of the states has three problems in common: security, human rights, and economic growth.